PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI OPERASI ALJABAR - M. Yunus (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2019)
This study aims to improve the learning outcomes of students of class VII-A MTs Negeri 2 Subang in Mathematics Subjects in algebraic operating material. This type of research is classroom action research conducted in two cycles, each cycle carried out in 2 meetings. Each meeting consists of the stages of planning, action, observation, and reflection. The subjects in this study were all students of class VII-A MTs Negeri 2 Subang odd semester academic year 2018-2019 which amounted to 34 students. Data obtained in this study include: learning outcomes and student learning completeness taken from giving test questions at the end of each meeting and activeness of students in the learning process takes place. From the research results data obtained the average student learning outcomes in the first cycle is 78.53 and the second cycle is 95.88. The average learning completeness in the first cycle is 74% and the second cycle is 100%. From these data it is clear that from cycle I to cycle II there is a significant increase. From this study, it was concluded that using the jigsaw type cooperative learning model could improve the learning outcomes of students of class VII-A MTs Negeri 2 Subang in Mathematics Subjects in algebraic operations.